THE COMMUNITY DEVELOPMENT PROGRAM OF THE INTERNATIONAL HUMAN RIGHTS MOVEMENT PHILIPPINES (IHRM-PHILS, INC) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The Philippines now is suffering from a great economic loss because of the increasing number of infected persons from COVID-19 because of that numerous establishment were closed down and a lot of workers' lost their jobs that is why a very alarming increasing in poverty is experienced. The International Human Rights Movement Philippines is a newly created group which is registered under the Security Exchange Commission (SEC), one of the mission of the organization is aligned to the UN SDG pertaining to Community Development Program that can aid the ongoing situation.